Sistem Pendukung Keputusan Penentuan Starting Five Pemain Basket Club Koba Utama Menggunakan Metode Simple Additive Weighting (Saw) - Bayu Bayuni; Novri Hadinata (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Utilization of information technology in the world of sports, especially in basketball, especially in selecting effective players to match the desired characters and criteria is still not optimal because it still does not have a comprehensive computerized system that can provide information, which is able to provide alternatives. options for coaches for decision making. In (Dwi Sasongko, Aries, 2014) Many basketball clubs have not used information technology in decision support, one of which is the Koba Utama Basketball Club. Koba Utama Basketball Club is the only basketball team in Koba City, Central Bangka Regency, Bangka Belitung Province. In the process of selecting 5 players as the core team in a Basketball match at the Club, it is still done based on the observations and assessments of the coach in the field. Where the players must have the value of the abilities possessed by each player and 5 players will be selected who will become Start Five in a certain period of time. So the problem is that it will be difficult to choose the right players where there are many players who have relatively the same ability. This study describes the process of designing a decision support system to determine the Starting Five of Club Koba Utama basketball players using Simple Additive Weighting (SAW). The Simple Additive Weighting (SAW) method is used to assist the Chair/Coach of the Koba Utama Basketball Club in determining five basketball players, in order to get players who fit the required criteria more efficiently than the usual/manual method. The player information in the system is the information provided by the Chairman/Coach of the Main Koba Club. The final results in this study support decisions that are built in accordance with the purpose of helping especially the Chairman/Coach of the Koba Utama Club in the process of Starting Five basketball players. RUP (Rational Unified Process) is a process framework that provides industrial system simulation for systems, software, implementation, and effective project management and is also a software development approach with an iterative approach and use-case driven modeling. Decision Support System Starting Five-Based Web With the existence of the Start Five basketball decision support system at Club Koba Utama, it can help the chairman/coach of the Koba Utama Basketball Club to determine the Starting Five core players. As a tool that can help the business process at the Koba Utama Basketball Club to activate Lima to be more effective and efficient. Keywords: Start Five Decision Support System, Simple Additive Weighting, Rational Unified Process (RUP)